Cortical dynamics within and between parietal and motor cortex in essential tremor. Issue 1 (21st October 2018) - Roy, Arnab; Coombes, Stephen A.; Chung, Jae Woo; Archer, Derek B.; Okun, Michael S.; Hess, Christopher W.; Wagle Shukla, Aparna; Vaillancourt, David E.
ABSTRACT: Background: Evidence from functional imaging in essential tremor suggests that activity within parietal and motor cortices may be associated with worsening of tremor at increased visual feedback. Objectives: Examine how cortical oscillations within these regions and the connectivity between these regions is associated with worsening of tremor in essential tremor in response to high visual feedback. Method: The study included 24 essential tremor participants and 17 controls. We measured cortical activity and tremor magnitude at low and high feedback conditions. Cortical activity was measured using high‐density electroencephalogram and isolated using source localization. Results: Changes in power across feedback in the 4–12 Hz and 12–30 Hz bands were reduced within the contralateral motor cortex of essential tremor patients compared to controls. The 12–30 Hz bidirectional connectivity between the parietal and contralateral motor cortex was decreased in essential tremor patients. Worsening of tremor from low to high visual feedback was associated with 4–12 Hz activity in contralateral motor cortex. The greatest separation between groups was found when using the difference of the contralateral motor cortex activity at high and low feedback, rather than either feedback condition alone. Conclusion: Our findings provide new evidence that tremor in essential tremor is associated with reduced power across feedback in the motor cortex and reduced connectivity between the parietal and motor cortices. Combined with previous work on the cerebellar‐thalamo‐cortical motor circuit, our findings suggest that the network level disturbances associated with essential tremor extend to the cortico‐cortical pathway between the parietal cortex and motor cortex. © 2018 International Parkinson and Movement Disorder Society